PENGARUH PEMODELAN SMOOTH PARTICLE HYDRODYNAMICS UNTUK APLIKASI SIMULASI NUMERIK BIRD STRIKE DI LEADING EDGE - S, Sahril Afandi; Franciscus, Freddy; Afrianto, Muhammad Faisal (JTK: JURNAL TEKNOLOGI KEDIRGANTARAAN, 2019)
Accidents due to bird strike often occur in flight operations and during the migratory period of birds, this can cause structural failure and threaten flight safety. The effect that occurs on the structural components of the aircraft affected by the collision of the bird hit is generally in the form of dent deformation or the perforation of the plane's skin layer and other structures. This study discusses bird strike in Leading Edge with SPH (smooth particle hydrodinamics) method based on finite element method. Leading Edge structure is assumed to only consist of skin by varying 4 bird speeds, namely: 75 m / s, 100 m / s, 125 m / s and 150 m / s, and 2 angular variations of 0o and 45o. The simulation results show the deformation of Leading Edge increases with increasing speed, and the impact force is higher in the direction of the 0o collision for each of the same speed. The maximum impact force at each speed for the collision direction is 0o and 45o in the range of 6 - 17 kN and 3 - 12 kN. While the maximum displacement results at each speed for collision directions are 0o and 45o in the range 148 - 336 mm and 89 - 198 mm.